AKIBAT HUKUM TERHADAP HARTA WARISAN YANG DIJUAL BELUM DIBAGI WARIS - Fatia Nuriza; Wiwiek Wahyuningsih (Private Law, 2023)
This study aims to determine the validity of the sale and purchase agreement for inherited assets that have not been sold and to analyze and find out the judge's considerations in Decision Number 0406/Pdt.G/2013/PA Pre regarding the legal consequences of inherited assets that have not been sold as inheritance. This research was carried out by applying normative legal research methods using a statutory approach (statute approach), conceptual approach (conceptual approach), and case approach. The results of the study revealed that the validity of the sale and purchase agreement for inherited assets that are sold without inheritance must comply with the provisions of Article 1320 of the Civil Code, as a result selling inheritance that has not been divided into inheritance cannot be said to be valid because it does not meet the objective requirements, namely the existence of certain things and lawful causes that causing the sale and purchase agreement to be null and void because it contradicts the provisions of Article 1334 paragraph (2) of the Civil Code and the results of the research revealed that the judge's consideration in Decision Number 0406/Pdt.G/2013/PA Pre related to legal consequences of the inheritance sold has not been divided into inheritance namely the Panel of Judges ordered the Defendants and Co-Defendant to hand over the inheritance to all the heirs who are entitled and if it cannot be divided in kind then it can be done by way of auction through the State Auction Agency in accordance with Article 200 paragraph (1) HIR or Article 215 paragraph ( 1) RBg.